2016
DOI: 10.3174/ajnr.a4741
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Anatomic Variations Require an Adaptable Approach during Intra-Arterial Chemotherapy for Intraocular Retinoblastoma: Alternative Routes, Strategies, and Follow-Up

Abstract: BACKGROUND AND PURPOSE: Intra-arterial chemotherapy for retinoblastoma is not always a straightforward procedure, and it may require an adaptable approach. This study illustrates strategies used when the ophthalmic artery is difficult to catheterize or not visible, and it ascertains the effectiveness and safety of these strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 23 publications
1
58
1
Order By: Relevance
“…Apparently, some of them may appear (i.e. become detectable) under particular hemodynamic circumstances [5, 16]. Thus, it is important to ascertain how powerful angiography is to unveil orbital anastomoses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, some of them may appear (i.e. become detectable) under particular hemodynamic circumstances [5, 16]. Thus, it is important to ascertain how powerful angiography is to unveil orbital anastomoses.…”
Section: Introductionmentioning
confidence: 99%
“…This parameter, referred to as the visibility index (VI) (see materials and methods), has been recently introduced to ascertain the ability of angiography to visualize and identify intraorbital arteries [9]. Unfortunately, as it will become apparent in the next paragraphs, in spite of the fact that orbital anastomoses are acknowledged of pivotal importance in several clinical scenarios [5, 17, 34], only limited information on their frequency are available, so that the VI can be calculated just in a small number of cases.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Since then, several investigators have reported their experience with IAC. [131415161718192021222324252627282930] In a study done by Tuncer et al ., 26 Group D eyes of 24 treatment-naïve Rb patients managed primarily with IAC were included. [19] Each eye received a mean of three IAC sessions/eye (range, 2–5 sessions).…”
Section: Globe-saving Treatmentsmentioning
confidence: 99%
“…illustrates strategies used when the ophthalmic artery is difficult to catheterize or not visible, and it ascertains the effectiveness and safety of these strategies. [28] They recognized three different patterns of drug delivery: a fixed pattern through the ophthalmic artery, a fixed pattern through branches of the external carotid artery, and a variable pattern through either the ophthalmic or the external carotid artery. Alternative routes of IAC for intraocular Rb appeared in the short term as effective and safe as the traditional drug infusion through the ophthalmic artery.…”
Section: Globe-saving Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation